Characteristics of Analog Satay Based on Tempeh Protein Isolate (Rhizopus oryzae) and Oyster Mushroom (Pleurotus ostreatus) - Amelia HK, Lenny; Albiansyah, Rizky (Corespub, 2025)
Development of analog meat products using local ingredients such as tempeh and oyster mushrooms presents an innovative solution to meet the demand for sustainable plant-based proteins. This study aimed to analyze the physicochemical, organoleptic, and functional characteristics of satay analogs made from tempeh protein isolate (Rhizopus oryzae) and oyster mushrooms (Pleurotus ostreatus). The tempeh protein isolate was obtained through an alkali-acid extraction process and then formulated with finely ground oyster mushrooms in various ratios (70:30, 50:50, 30:70). Based on the research, the satay analog made from tempeh protein isolate and oyster mushrooms with an optimal formulation of 70% tempeh isolate and 30% oyster mushrooms yielded a product with high protein content (36.79%) and a texture resembling real meat, as indicated by a peak load of 250-300 g-force in texture analysis. In terms of organoleptic properties, the product received high preference scores across all parameters, particularly for its natural red-brown color derived from angkak (red yeast rice), umami flavor, savory aroma characteristic of tempeh and mushrooms, and a chewy texture favored by panelists. The product's advantages lie in its use of highly nutritious local ingredients, safe natural coloring, and its ability to mimic the characteristics of real meat.